Pengembangan Lembar Kerja Peserta Didik (LKPD) Dengan Berorientasi Problem Based Learning (Pbl) Pada Materi Pengumpulan Dan Penyajian Data Kelas V Di SD Negeri 08 Pontianak Selatan - Sari Maya; Kartono Kartono; Salimi Asmayani (Journal on Education, 2024)
This research aims to produce probllem based learning oriented student worksheet product on appropritate material for coellecting and presenting data for class V elementry schools. The research method used is research and development (RnD) by adapting the Thiagarajan 4D development model (define, design, development and dissemination). The data sources for this research are the validation results from three validators, the results of student respons questionnaires and the results of student worksheet trials. The data collection techniques for this research are validator validation questionnaires, students response questionnaires, and student worksheet documentation used by teachers. The research results show that during the process of developing problem based learning oriented student worksheet, it was carried out in only three stages, namely the define, design and development stages. The average percentage validity of student worksheet from the language aspect is 4 with very valid criteria from the learning (material) aspect or 4.1 with very valid criteria, from the technical/apperarance aspect it is 4.2 with very valid criteria. Furthermore, the results of small-scale students respons obtained an average percentage of 77,75% with good criteria and large scale test obtanied an average percentage of 89,5% with very good creteria.